THE EARLIEST CHINESE WORKBOOK FOR ACCORDION - Huang, In (E-Journal VFU, 2025)
The accordion enters China from the middle of the 19th century during the historical development of the cultural exchange with the West. Many books dedicated to this instrument were written, translated, and published in the earliest stages of the accordion art in the country. This article researches the earliest Chinese “Workbook for Accordion” in detail, offering a wide perspective to the specific situation in the beginning of the development of the accordion art in China.